Myopathy with Concurrent Tadalafil and Simvastatin - Maria Pia Gargante; Marco Vacante; Cristina Russo; Mariano Malaguarnera (Case Reports in Medicine)
A 48-year-old man, using statin, was admitted to hospital with progressive myalgia after consumption of tadalafil and simvastatin. Muscle pain and penile erection disappeared seven days after interruption of therapy. This case demonstrates the interaction of tadalafil with simvastatin resulting in myopathy. Muscle damage could be attributed to the common metabolic way of these two drugs which is cytochrome P450 isoenzyme system.